Colistin–niclosamide-loaded nanoemulsions and nanoemulsion gels for effective therapy of colistin-resistant Salmonella infections - Zhang, Junkai; Wang, Xilong; Li, Pengliang; Gao, Yanling; Wang, Ruiyun; Li, Shuaihua; Yi, Kaifang; Cui, Xiaodie; Hu, Gongzheng; Zhai, Yajun (Frontiers in Veterinary Science, 2024)
Colistin (COL) is regarded as a last-resort treatment for infections by multidrug-resistant (MDR) Gram-negative bacteria. The emergence of colistin-resistant Enterobacterales poses a significant global public health concern. Our study discovered that niclosamide (NIC) reverses COL resistance in Salmonella via a checkerboard assay. However, poor solubility and bioavailability of NIC pose challenges. In this study, we prepared a self-nanoemulsifying drug delivery system (SNEDDS) co-encapsulating NIC and COL. We characterized the physicochemical properties of the resulting colistin–niclosamide-loaded nanoemulsions (COL/NIC-NEs) and colistin–niclosamide-loaded nanoemulsion gels (COL/NIC-NEGs), assessing their antibacterial efficacy in vitro and in vivo. The COL/NIC-NEs exhibited a droplet size of 19.86 nm with a zeta potential of −1.25 mV. COL/NIC-NEs have excellent stability, significantly enhancing the solubility of NIC while also demonstrating a pronounced sustained-release effect. Antimicrobial assays revealed that the MIC of COL in COL/NIC-NEs was reduced by 16–128 times compared to free COL. Killing kinetics and scanning electron microscopy confirmed enhanced antibacterial activity. Antibacterial mechanism studies reveal that the COL/NIC-NEs and COL/NIC-NEGs could enhance the bactericidal activity by damaging cell membranes, disrupting proton motive force (PMF), inhibiting multidrug efflux pump, and promoting oxidative damage. The therapeutic efficacy of the COL/NIC-NEs and COL/NIC-NEGs is further demonstrated in mouse intraperitoneal infection models with COL-resistant Salmonella. To sum up, COL/NIC-NEs and COL/NIC-NEGs are a potentially effective strategies promising against COL-resistant Salmonella infections.